Patient Blood Management as Standard of Care. (October 2016) - Shander, Aryeh; Bracey, Arthur W.; Goodnough, Lawrence T.; Gross, Irwin; Hassan, Nabil E.; Ozawa, Sherri; Marques, Marisa B.
Abstract : Published ahead of print August 2, 2016.